2018
DOI: 10.1016/j.juro.2018.05.094
|View full text |Cite
|
Sign up to set email alerts
|

Added Value of Multiparametric Magnetic Resonance Imaging to Clinical Nomograms for Predicting Adverse Pathology in Prostate Cancer

Abstract: Magnetic resonance imaging alone or in addition to standard clinical nomograms provides significant additional predictive ability of adverse pathology at the time of radical prostatectomy. This information can be greatly beneficial to urologists for preoperative planning and for counseling patients regarding the risks of future therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
58
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 25 publications
4
58
2
Order By: Relevance
“…Regardless of the radiologist experience, the combination of clinical models and mpMRI provided significantly robust tools in terms of discriminatory power, and increased the AUCs compared with clinical models alone. This is in line with previous results on EPE by Morlacco et al using PT (AUC from 0.61 to 0.73) and CAPRA (AUC from 0.69 to 0.77), Feng et al using PT (AUC from 0.85 to 0.93) and MSKCCn (AUC from 0.86 to 0.94), as well as Ryan et al using MSKCCn (AUC from 0.70 to 0.80) and PT (AUC from 0.66 to 0.80) in a subpopulation of patients undergoing systematic biopsy without image fusion. In contrast, Weaver et al found no incremental value of mpMRI compared with MSKCCn.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Regardless of the radiologist experience, the combination of clinical models and mpMRI provided significantly robust tools in terms of discriminatory power, and increased the AUCs compared with clinical models alone. This is in line with previous results on EPE by Morlacco et al using PT (AUC from 0.61 to 0.73) and CAPRA (AUC from 0.69 to 0.77), Feng et al using PT (AUC from 0.85 to 0.93) and MSKCCn (AUC from 0.86 to 0.94), as well as Ryan et al using MSKCCn (AUC from 0.70 to 0.80) and PT (AUC from 0.66 to 0.80) in a subpopulation of patients undergoing systematic biopsy without image fusion. In contrast, Weaver et al found no incremental value of mpMRI compared with MSKCCn.…”
Section: Discussionsupporting
confidence: 92%
“…However, they match with those found by Morlacco et al on a population with more advanced disease at diagnosis (Gleason score 8 or larger and high risk at the D'Amico classification in 44% and 55.8% of cases, respectively), thus indirectly suggesting that mpMRI can be effectively added to clinical models in different clinical populations. Of note, we found a prevalence of pathology‐proven EPE of 32.9%, ie, within the range of previous studies (21.6–42.3%) …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations